Tomato lycopene prevention of alcoholic fatty liver disease and hepatocellular carcinoma development - Camilla P. Stice (KeAi Communications Co., Ltd., 2018)
Alcoholic liver disease (ALD) is a major cause of morbidity and mortality worldwide. The incidence of hepatocellular carcinoma (HCC) is increasing in the United States, and chronic, excessive alcohol consumption is responsible for 32%–45% of all the liver cancer cases in the United States. Avoidance of chronic or excessive alcohol intake is the best protection against alcohol-related liver injury; however, the social presence and addictive power of alcohol are strong. Induction of the cytochrome P450 2E1 (CYP2E1) enzyme by chronic and excessive alcohol intake is known to play a role in the pathogenesis of ALD. High intake of tomatoes, rich in the carotenoid lycopene, is associated with a decreased risk of chronic disease. The review will overview the prevention of ALD and HCC through dietary tomato rich in lycopene as an effective intervention strategy and the crucial role of CYP2E1 induction as a molecular target. The review also indicates a need for caution among individuals consuming both alcohol and high dose lycopene as a dietary supplement. Keywords: Tomato, Lycopene, Alcoholic liver disease, Liver cancer, CYP2E1